The Unspoken Possibility of Language: Poetic Silence in Mallarmé and Rilke - Trogan, Christopher Roland (Pivot: A Journal of Interdisciplinary Studies and Thought, 2014)
Recent and competing definitions of “modernity” all point to a fundamental characteristic which has been explored and theorized time and again but deserves still more intellectual attention: the ambivalence towards language unparalleled by anything written before the nineteenth century. On the one hand, “modernity” has placed great faith in the power of the word; however, this faith has been overwhelmed with enough suspicion to undermine any potential linguistic stability. In its most extreme manifestation, this results in a phenomenon of linguistic anxiety, even paranoia, which threatens the semantic possibilities of poetics. The resulting threat of silence – whether thematic, syntactical, metaphoric, or literal – is ubiquitous in modern poetry. As Eliot writes, “words, after speech, reach into silence.” An analysis of the general phenomenon of poetic silence and of two modern responses to it – those of Mallarmé and Rilke – yield significant insights both into the idea of the “modern” as well as into the essence and inner machinations of modern poetry.